A Fuzzy Method for Exploring Key Factors of Smart Healthcare to Long-Term Care Based on Z-Numbers - Chen-Tung Chen; Chien-Chi Chu (Mathematics)
As the proportion of the population comprising the elderly cohort increases, so too does the demand for medical care for long-term conditions among this demographic. The advent of information technology and artificial intelligence has prompted a crucial examination of the potential of smart medical technology and equipment to enhance the quality of long-term care and the operational efficiency of long-term care facilities. The introduction of smart healthcare into long-term care is influenced by a few factors, and expert opinions often exhibit ambiguity and subjectivity in the evaluation process. As Z-numbers are capable of adequately expressing the ambiguity of expert assessments and the degree of certainty associated with them, they are employed in this study to convey the opinions of the experts. Furthermore, the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method is an effective approach to analyzing the relationships between factors. Consequently, this study integrates the Z-numbers and DEMATEL methods for empirical analysis. The present study focuses on two long-term care institutions with different natures as empirical subjects. The findings of the study indicate that Institution A identifies the “Internet of Things” as the most pivotal key factor, whereas Institution B deems “Smart clinics and urgent care centers” to be the most crucial key factor. The analysis demonstrates that three factors—global positioning systems, telemedicine, and electronic medical records—are all regarded as significant influencing factors for different long-term care institutions. Consequently, the analytical model of this study is not only theoretically sound but also effective in identifying the key factors and importance of introducing smart healthcare into long-term care institutions.